Sosialisasi Edukasi Literasi Keuangan Pasar Modal Bagi Masyarakat Kelurahan Srengseng Sawah Kecamatan Jagakarsa Jakarta Selatan - Nana Nawasiah; Hotman Freddy; Roy Prakoso (FEB-UP Press, 2019)
Public awareness, interest and knowledge of the Capital Market is still very low. In an effort to introduce to the public related activities in the capital market, socialization activities are needed. Capital Market Socialization was carried out in the Srengseng Sawah Village District of Jagakarsa District, which was the first activity of capital market socialization. This capital market socialization is one of the education programs which is expected to increase public awareness and interest in the capital market, so that the number of investors in Indonesia can increase and the investment climate becomes better to improve the Indonesian economy. In addition, the community is getting smarter in investing their funds, and is expected to provide benefits for family welfare.